2021
DOI: 10.3389/fimmu.2021.639735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neutrophil-to-Lymphocyte Ratio Combined With Interleukin-6 in Predicting 28-Day Mortality in Patients With Sepsis

Abstract: BackgroundThe current study aimed to evaluate the relationship between the neutrophil-to-lymphocyte ratio (NLR) combined with interleukin (IL)-6 on admission day and the 28-day mortality of septic patients.Material and MethodsWe conducted an observational retrospective study. Patients with presumed sepsis were included. We observed the correlation of studied biomarkers (NLR, IL-6, PCT, and CRP) and the severity scores (APACHE II and SOFA scores) by plotting scatter plots. The relationships of the studied bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…Recently, several reports have documented the potential utility of NLR as a diagnostic parameter that is closely related to miscellaneous diseases, including inflammation, ischemic cerebrovascular disease, cancer, and trauma ( 20 , 35 40 ). In our observational study, we found that NLR in patients who died were remarkably elevated compared with those with mild cases ( P < 0.01) ( 41 ), which is in accordance with the previous study showing that an inflammatory reactive state typically led to neutrophilia and relative lymphocytopenia ( 42 ). The AUC value of NLR corresponded to 0.827 with 69.62% sensitivity and 89.74% specificity at the optimal cutoff value of 5.51.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recently, several reports have documented the potential utility of NLR as a diagnostic parameter that is closely related to miscellaneous diseases, including inflammation, ischemic cerebrovascular disease, cancer, and trauma ( 20 , 35 40 ). In our observational study, we found that NLR in patients who died were remarkably elevated compared with those with mild cases ( P < 0.01) ( 41 ), which is in accordance with the previous study showing that an inflammatory reactive state typically led to neutrophilia and relative lymphocytopenia ( 42 ). The AUC value of NLR corresponded to 0.827 with 69.62% sensitivity and 89.74% specificity at the optimal cutoff value of 5.51.…”
Section: Discussionsupporting
confidence: 92%
“…In our observational study, we found that NLR in patients who died were remarkably elevated compared with those with mild cases (P < 0.01) (41), which is in accordance with the previous study showing that an inflammatory reactive state typically led to neutrophilia and relative lymphocytopenia (42). The AUC value of NLR corresponded to 0.827 with 69.62% sensitivity and 89.74% specificity at the optimal cutoff value of 5.51.…”
Section: Discussionsupporting
confidence: 90%
“…The authors proposed a NLR cut-off value of 5 for diagnosis of infection or sepsis when exclusion criteria are used [ 21 ]. A recent observational study demonstrated that NLR and IL-6 appeared to be independent predictors of 28-day mortality in septic patients [ 22 ]. Moreover, Jang et al conducted a clustering analysis showing that age, NLR and delta neutrophil index (DNI) were the most robust predictors for sepsis status in all subjects, as well as in cluster-specific groups [ 23 ].…”
Section: Nlr and The Pathophysiology Of Inflammatory Diseasementioning
confidence: 99%
“…Leukocyte markers reflecting the changes in immune cell subpopulations can be potentially helpful ( 165 ). Meanwhile, the combined use of indicators like neutrophil-to-lymphocyte ratio and monocyte/high-density lipoprotein cholesterol ratio reportedly has a better performance in predicting mortality for septic patients than a single parameter did ( 166 168 ). Although numerous studies have documented that immune monitoring indicators can predict multiple clinical endpoints for septic patients, including short- or long-term mortality, hospital-acquired infections, and organ dysfunction, basically no specific biomarkers are found to achieve a consistently good performance in predicting all these outcomes ( 5 ).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%